Exploitation of the IPHAS to Investigate Planetary Nebulae - Sabin, Laurence; Toalá, Jesús A.; Ramos-Larios, Gerardo; Guerrero, Martín A. (Frontiers in Astronomy and Space Sciences, 2022)
Similarly to other classes of astronomical objects, there is a large discrepancy between the total count of theoretically predicted Planetary Nebulae (PNe) and the number of those actually observed. This discrepancy introduces a bias in our attempt to globally understand and characterise the PN population. Major efforts have been made to find the missing PNe. In particular the INT Photometric Hα Survey (IPHAS) has, since its debut, provided a whelms of new (candidates) PNe, some of which have been studied in depth using various methodologies such as deep imaging, and low- and high-resolution spectroscopy. Here we present the outcome of the analysis of a first group of these well investigated IPHAS PNe with a focus on the extended ones. We show that in general the missing objects that were expected to be unveiled by the survey (low density, evolved, distant) are indeed discovered, but the survey also allows the retrieval of “simply” overlooked PNe.